(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article provides an in-depth analysis of the theoretical, institutional, and practical aspects of state regulation and supervision over the investment activities of insurance companies. As an integral part of the financial markets, the insurance sector plays a significant role not only in ensuring the financial stability of individuals and economic entities but also in mobilizing investment resources and directing them toward the real sector of the economy. From this perspective, the establishment of an effective state control and regulatory system over the investment activities of insurance companies holds both scientific and practical relevance. The article examines the requirements, restrictions, and monitoring mechanisms applied to the investment activities of insurance companies based on international experience and identifies current challenges and barriers in Uzbekistan’s insurance market. Specifically, the implementation and effectiveness of state-imposed regulatory and legal requirements concerning investment diversification, liquidity, capital adequacy, risk assessment systems, and information transparency are assessed. The study analyzes both direct (through regulatory authorities) and indirect (through legal norms, tax incentives, and administrative requirements) state intervention tools aimed at minimizing investment risks, ensuring financial stability, and fostering a healthy competitive environment. Furthermore, the author proposes specific recommendations for institutional reforms that need to be undertaken by the state in order to fully unlock the investment potential of insurance companies in Uzbekistan. These include the introduction of modern financial monitoring systems, the implementation of rating mechanisms based on international standards, and the strengthening of corporate governance.